STUDI ISLAM INTERDISIPLINER: SEBUAH KENISCAYAAN - Mujtaba, Saifuddin (Universitas Nurul Jadid, 2015)
This study portrays interdisciplinary Islamic studies as an undeniable necessity, since it argues that Islam had produced many scientific disciplines and approaches to be studied under various aspects. This interdisciplinary approach was firstly coined by Harun Nasution in the 1980s and achieved the better situation in terms of that doctrinal-traditional studies are not sufficient for the Islamic studies, then it needs to develop the interdisciplinary subjects.